2019
DOI: 10.1097/j.pbj.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

The electronic nose technology in clinical diagnosis: A systematic review

Abstract: Background: Volatile organic compounds (VOC) are end products of human metabolism (normal and disease-associated) that can be mainly excreted in breath, urine, and feces. Therefore, VOC can be very useful as markers of diseases and helpful for clinicians since its sampling is noninvasive, inexpensive, and painless. Electronic noses, or eNoses, provide an easy and inexpensive way to analyze gas samples. Thus, this device may be used for diagnosis, monitoring or phenotyping diseases according to specific breathp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 89 publications
1
77
0
1
Order By: Relevance
“…It has therefore been argued that this "black box" approach relies too heavily on pattern-recognition algorithms [157]. Moreover, this method cannot yield a targeted VOC biomarker test for the diagnosis of a particular condition or disease [158]. In this case, it is true that the eNose approach cannot identify unique biomarkers for UTI.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been argued that this "black box" approach relies too heavily on pattern-recognition algorithms [157]. Moreover, this method cannot yield a targeted VOC biomarker test for the diagnosis of a particular condition or disease [158]. In this case, it is true that the eNose approach cannot identify unique biomarkers for UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Sistem hidung elektronik (electronic nose (e-nose)) merupakan sistem elektronik yang terdiri dari beberapa jenis komponen sensor yang digunakan sebagai pendeteksi aroma [12,13]. Sensor gas memiliki prinsip kerja berupa perubahan tahanan, Surface Accoustic wave (SAW) yang menyebabkan perubahan nilai tegangan dan arus serta output berupa perubahan frekuensi, Quartz crystal microbalance (QCM ) ketika kadar unsur dan senyawa gas berubah [14,15]. Unsur dan senyawa gas berbahaya yang dimonitor dan dikontrol pada penelitian ini adalah gas Carbonmonoxide (CO) dan Carbondioxide (CO2).…”
Section: Pendahuluanunclassified
“…What is the performance of eNoses for diagnosing, phenotyping, and monitoring respiratory diseases? Even though the reported accuracies for various diagnoses are relatively good, 3 there are not many studies that have demonstrated replication of data in an independent population (external validation). The latter is required to confirm the quality and clinical value of the observations.…”
mentioning
confidence: 99%
“…After appropriate sensor selection, these properties make eNose ''breathprints'' suitable as composite multidimensional biomarkers, providing numerical probabilities for the presence or absence of a particular clinical condition. 3 The large advantage of this technology is its noninvasiveness and ease-to-use, while the results can be made readily available in the doctor's office by eNoses that are linked to online cloud computing 4 (Fig 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation